Development and Validation of a Highly Sensitive HPLC Method for Determination of Paclitaxel in Pharmaceutical Dosage forms and Biological Samples - Bernabeu, Ezequiel; Flor, Sabrina; Hocht, Christian; Taira, Carlos; Chiappetta, Diego; Tripodi, Valeria; Lucangioli, Silvia (Current Pharmaceutical Analysis, 2014)
A new simple and highly sensitive HPLC-UV method for the analysis of paclitaxel in Taxol® and Abraxane® has been developed which also allows the quantification in biological samples of pharmacokimnetic studies with a very easy sample preparation. The proposed method has advantages over previously reported methods, such as an increase in sensitivity up to 20 times, good accuracy in terms of recovery that allows to work without addition of internal standard and a simple sample preparation in one step. The analysis was carried out using a Zorbax Eclipse XDB-C18 (4.6 × 150 mm, 3.5 μm) with a column guard. The mobile phase consisted of acetonitrile: water (50: 50) and the flow rate was 1 mL/min, the detection wavelength was 227 nm, the injection volume 5 μL and the analysis was performed at room temperature. The method was validated according ICH guidelines and FDA guidelines for validation of bioanalytical methods. Linearity was evaluated in the range from 0.005 – 50.0 μg/mL, with a regression coefficient (R2) of 0.9967. LOD and LOQ were 0.001 and 0.005 μg/mL respectively.
Keywords: Paclitaxel